Influence Of Activated Carbon On Total Suspended Solids And Relative Plugging Index Of Injection Water From X-Oilfield - Tjuwati Makmur (Testing Center for Oil and Gas LEMIGAS, 2013)
Produced water will be used as injection water for water flooding need, but, based on the results of water quality tests show poor injection water quality caused by a lot of solids particles with high total suspended solids (TSS) concentration and high relative plugging index (RPI) obtained in the injection water. When, the condition of injection water without treatment is injected into formation will cause serious plugging. In this study, two methods used to minimize the high TSS and RPI problems are treatment with chemical and filtration (activated carbon). The use of optimal concentration of scale inhibitor in the injection water can reduce TSS and RPI in the injection water, but it does not work effectively, so that its water quality is still poor water quality and can cause plugging in the formation. Another method is filtration with activated carbon filter media which has characteristics of adsorption and large specific area to filter insoluble materials in the injection water. After filtration, the filtrate of the injection water results in clear water condition. Based on the results of laboratory tests indicate that the filtrate of the injection water contains the least solids particles with small particle size, low total suspended solids concentration and low relative plugging index value. When, it is injected into formation, the possibility of plugging occurrence can be minimized, although, there is increase of pH value, but, in general, the filtrate of the injection water can be categorized good water quality